Phenotypic correlations and path analysis for plant architecture traits and grain production in three generations of cowpea - Ribeiro, Hugo Leonardo Coelho; Santos, Carlos Antônio Fernandes; Diniz, Laerte da Silva; Nascimento, Layana Alves do; Nunes, Edna Deodato (Revista Ceres, 2016)
The objective of this study was to analyze the phenotypic correlation and path analysis of traits related to plant architecture, earliness and grain yield in F2, RC1 and RC2 generations, from crosses between cowpea cultivars BRS Carijó and BR14 Mulato. Most phenotypic correlations of the examined traits were concordant in statistical significance, with approximate values among the examined generations. For the trait seed weight, significant and positive phenotypic correlations were observed in the three generations only for the trait number of secondary branches. The values of the direct effects were in agreement with the values of the phenotypic correlations, which indicate true association by the phenotypic correlation among the traits of grain yield examined. Path analysis indicated that the selection of productive plants will result in early plants and an increased number of secondary branches. In F2, plants with shorter length of the main branch and shorter length of secondary branches can be obtained. The causal model explained 15 to 30% of the total variation in grain weight in relation to the traits examined. The analyses indicated the possibility of selecting plants with a higher and early grain yield, shorter length of primary branches and lower number of nodes, which are important variables for mechanical or semi-mechanical harvesting.